Liminality, possibility, and imperative: Performing the other in face transplantation (Medicine Anthropology Theory, 2015)
This piece seeks to expand the notion of liminality within medical anthropology by shifting attention to how in-between states are actively produced and performed by medical experts. While medical anthropologists have successfully engaged with the notion of liminality to make sense of patient experience, I suggest that it holds broader potential and can be used to examine the production of medico-political imperatives by clinical elites. To do this, I trace shifting ideas surrounding the need to utilize face transplantation as it relates to the promotion of an institutionally produced category – the ideal patient. While once the 'ideal patient' was seen as a panacea to the ethical issues at stake in the performance of the operation, it arguably now works to limit the ability of surgeons to utilize face transplants to reconstruct the appearances of severely disfigured people. In response, leading face transplant surgeons tactically emphasize the problematizing state of their patients who occupy the limen of life and death. They ascribe sick roles to individuals in order to afford agentive, moral force to (bio)ethically fraught experimental medicine.